Pengaruh Nilai Simbolis dan Utilitarian Persepsian pada Sikap Konsumen dan Niat Beli - Rita Rita (Binus Business Review, 2011)
Brand makes easier consumer to take efficiently purchase decision about the product. Consumer choices product or brand are driven by utilitarian and hedonic considerations. The main purpose of this study was to examine the effect of perceived symbolic value and utilitarian value on consumer attitudes toward brand and purchase intentions. The respondents in this study are university students in Yogyakarta. Sampling technique used was purposive sampling. There are only 235 respondents among 400 questioners whom can be used as samples. Validity and reliability testing were conducted in order to figure out the validity rate and data reliability. The data were analyzed by using Regression Analysis. The results provide support for seven of the eight hypothesized. The results provide that symbolic value and utilitarian value as two different value but related. The results show that symbolic value and utilitarian value have a positive impact on consumer attitudes toward brand and purchase intentions.